Chemokine (C–C motif) receptor 2 is associated with the pathological grade and inflammatory response in IgAN children - Yanjie Shen; Zhiqing Zhu; Rui Wang; Lili Yan; Shuaichen Sun; Ling Lu; Zhenhua Ren; Qin Zhang (BMC Nephrology, 2022)
Abstract Background Chemokine (C–C motif) receptor 2 (CCR2) is involved in important physiological and pathological processes, such as inflammation and autoimmune diseases. Abnormal immune and inflammatory responses play a critical role in the development and progression of IgA nephritis (IgAN). However, the role of CCR2 in IgAN is unknown. Methods Fifteen IgAN children who were diagnosed by kidney biopsy provided kidney biopsy tissue, blood and urine samples, and age-matched healthy control subjects (blood donators n = 12; tissue donators n = 8) were included. Immunohistochemical analysis was used to detect the expression of CCR2, MCP-1, IL-6, IL-17, and TNF-α in the kidney tissues. Relative optical density (OD) was calculated by Image J software, and the correlation between CCR2 expression and pathological grade in IgAN children was analyzed. Results The expression of CCR2 significantly increased in mesangial cells of children with IgAN compared to that in control group (P < 0.001), especially in IgAN patients with Lee’s grade III to IV (P < 0.001). Interestingly, CCR2 expression was positively correlated with Lee’s grade (r = 0.9152, P = 0.0001) in IgAN children. The expression levels of inflammatory factors were markedly increased in IgAN children, and importantly CCR2 expression was positively correlated with it’s expression level. Conclusions The results suggest that CCR2 signaling might be involved in pathological process and inflammatory responses of children IgAN, and could potentially be an intervention target in children IgAN.